Synergy of Environmental Education Programs at The Bodogol Nature Conservation Education Center, Complementing The Independent Curriculum at Junior High Schools - Soekmadi, Rinekso; Aprilia, Hapriza; Arifin, Hadi Susilo (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The global environmental crisis needs fundamental changes in people's attitudes and behaviors towards sustainability. The Bodogol Nature Conservation Education Center (PPKAB) in Gunung Gede Pangrango National Park has significant potential to support environmental education but remains underutilized due to a lack of integration with school curricula. The research problem is that PPKAB’s programs are not fully integrated, leading to suboptimal use and stagnant development. Purpose: This study aims to develop a synergy between PPKAB’s environmental education programs and the Independent Curriculum for junior high schools. Design/Methodology: The Study is a quantitative and descriptive qualitative. Utilizing the Analysis of Operational Areas and Natural Tourism Objects and Attractions (ADO-ODTWA) method, and involving ten including academics, business, community, government and media, the study assessed the feasibility and developed a synergy matrix. Findings/Result: The findings indicated a feasibility score of 76,3%, suggesting suitability for developing educational programs. The research recommends developing two environmental education synergy programs, namely School Visit Synergy and School Visits, to complement the independent curriculum at junior high school (SMP). Conclusion: As a conclusion, it is highly advised integrating PPKAB’s programs with school curricula to improve environmental education quality at the junior high level. This research produced significant results in environmental education.Originality/Value (State of the art): The added value of this research is that it emphasizes the business potential of ecotourism in supporting local economies and conservation efforts through strategic partnerships and innovative program development. Keywords: ecotourism, environmental education, independent curriculum, program synergy, the bodogol nature conservation education center